Roboguru
VT

Vania T

09 November 2020 03.20

f(x) =x² - 2x - 15 f(x) =x² - 8x + 16 f(x) = -3x² + 6x + 2 f(x) = x² + 6x +2 f(x) = -x² + 14x - 6

f(x) =x² - 2x - 15 f(x) =x² - 8x + 16 f(x) = -3x² + 6x + 2 f(x) = x² + 6x +2 f(x) = -x² + 14x - 6

0

1

Ruangguru

RUANGGURU HQ

Jl. Dr. Saharjo No.161, Manggarai Selatan, Tebet, Kota Jakarta Selatan, Daerah Khusus Ibukota Jakarta 12860

Coba GRATIS Aplikasi Ruangguru

Produk Ruangguru

Produk Lainnya

Hubungi Kami

Ikuti Kami

©2021 Ruangguru. All Rights Reserved